Electronic-photonic arithmetic logic unit for high-speed computing - Zhoufeng Ying (Nature Portfolio, 2020)
Integrated photonics allows integration of complex optical circuits on a single chip. Here, the authors propose a wavelength division multiplexing based electronic-photonic arithmetic logic unit for computing at high speeds and with improved power consumption to help with the physical limits of Moore’s law.